Computer science and educational games to enhancing students’ Islamic content learning - Tlili, Ahmed; Chikhi, Salim (Institute of Advanced Engineering and Science, 2025)
Learning in all humanities content branch such as Islamic sciences is declared to be boring, tiring and very dry plain content because the educational level of learners becomes low and worrying. This statement is justified by the result of our statistical study which reveals that learning of Islamic content is not attractive and needs to be revolutionized in order to make it more attractive and interesting for the new generation called digital generation. In this paper, we have used the gamification concept with learning analytics (LA) approach to design an educational game to improve Islamic content learning. However, and due to the lake of works and the knowledge about teaching Islamic contents using education games look insufficient and at their begins. The obtained results, in this study, with proposed approach, shows that the students had remarkably higher motivation and performance to learn than before. The main objective of this investigation is, firstly, allows managers and teachers easily incorporate LA approaches to help student improves their learning; and secondly, future work benefits from these results to define an appropriate dashboard for the Islamic content learning and teaching.